Effect of Swim Paddles on the Intra-Cyclic Velocity Variations and on the Arm Coordination of Front Crawl Stroke - Sidney, M.; Pelayo, M.; Pailette, S.; Hespel, J.-M.; Cholle, D. (coachesinfo.com, 2002)
This study analysed the effect of swimming with hand paddles on arm coordination and velocity pattern. Eight competitive swimmers performed two maximal aerobic tests. The maximal aerobic velocity was significantly higher when swimming with paddles but stroke rate, maximal heart rate and blood lactate values did not differ. The index of coordination (IdC) determined according to Chollet et al. (2000) and the intra-cyclic velocity variations were measured in two 25m tests, one with and one without swim paddles, at a fixed stroke rate. When swimming with paddles, IdC and the duration of the propulsive phase increased significantly (p<0.05) and the velocity signal frequency spectrum showed fewer harmonics (p<0.01). These results allowed to better understand the technical consequences of the swimming paddles versus free swimming.